The Alabaster Ceiling: The Gender Legacy of the Papal States - Elona Harka; Luca Nunziata; Lorenzo Rocco (Global Labor Organization (GLO), 2023)
We examine the gender legacy of past institutions by comparing Italian municipalities located in a narrow band across the borders between the former Papal States on the one hand, and the former Grand Duchy of Tuscany and the Duchy of Modena on the other. Our results show that a century after the dissolution of these pre-unification states, the municipalities once governed by the Papacy have lower female labor market participation and employment than their counterparts in Tuscany and Modena, while we find no discontinuity for males. We interpret these findings as the lingering effects of a deep-rooted conservatism that characterized the Papal States relative to the other preunification states, as confirmed by the analysis of the incidence of religious marriages, and voting patterns for a confessional political party and in two referenda on divorce and abortion rights. Our results also suggest that such a legacy is not permanent, although it takes centuries to dissipate.
Keywords: J16; J12; N9; P48; Z12; Z13; 330; Papal States; Gender Equality; Female Condition; Women Rights; Religion; Labour Market; Spatial Regression Discontinuity